Research on secure communication technology based on phase conjugate feedback chaotic injection system - Fu, Jingbo; Mu, Penghua (Journal of optics (2010), 2024)
This paper presents an experimental scheme using optical method instead of phase conjugate light. We have implemented a phase conjugate feedback semiconductor laser chaotic system based on the four-wave mixing principle through an established optical fiber experimental platform. Based on the high-dimensional wideband chaotic signals generated by this system, we propose a two-channel secure communication scheme based on phase conjugate feedback, and analyze its delay hiding mechanism and synchronization characteristics. The effects of parameter mismatch and injection strength on synchronization performance and communication quality are also considered. Our experimental results show that by adjusting the injection strength and frequency detuning parameters, the system can produce signals with time-delay signature completely suppressed, thus achieving high-quality and high-security communications.